Advanced theory and practice in sport marketing - Schwarz, Eric C.; Hunter, Jason D.; Brannigan, Kyle J.; Cattani, Kevin P.
"Now in a fully revised and updated fourth edition, Advanced Theory and Practice in Sport Marketing is still the only textbook to introduce key theory and best practice in sport marketing at an advanced level. The book goes beyond the introductory sport marketing course by exploring advanced marketing theories related to topics such ethics and social responsibility, international marketing, marketing research and information systems, data analytics, consumer behavior, product and logistics management, branding and brand management, sales management, promotions, social media and networking, destination marketing, and evaluating performance. New to this edition are sections on pricing structures and strategies, experiential marketing, new digital marketing communications and technology, emotional intelligence in sport marketing, and social entrepreneurship. This is also one of the first books to consider the challenges of sports marketing in a post-COVID world. Every chapter contains extended case studies and theory-to-practice insights from marketing professionals around the world. This is an essential textbook for courses on sport marketing, and invaluable recommended reading for any general course on sport business, sport management, sport development, or marketing. Ancillary resources include a test bank, PowerPoint slides, and a master syllabus".